PENERAPAN EARLY WARNING PADA LAYANAN ON CALL UNTUK EFISIENSI LAYANAN TERHADAP WAJIB PAJAK (STUDI KASUS UPTB UPPD TALIWANG) - ANDRI DARMANSYAH; UMAR UMAR; MUAMMAR KHADAFIE (GANEC SWARA, 2024)
This research aims to evaluate the implementation of the Early Warning system in on call services to improve service efficiency for taxpayers at UPTB UPPD Taliwang. The method used is a mixed method between quantitative and qualitative approaches (Mix Methods) with data collection through questionnaires distributed to taxpayers and interviews conducted with several informants. Data were analyzed using descriptive statistics to see trends in perception and to test the validity, reliability and correlation of the relationship between Early Warning implementation and service efficiency. The research results show that the implementation of the Early Warning system significantly increases the efficiency of on call services at UPTB UPPD Taliwang. Taxpayers involved in this study felt an increase in timeliness, quality of communication, and handling of problems related to their tax obligations. In conclusion, the Early Warning system plays an important role in increasing the effectiveness and efficiency of on call services, so it is recommended that relevant agencies continue to develop and expand the implementation of this system to support improved public services.